Rekonstruksi Fikih Ekosentrisme: Revitalisasi Konsep Hima sebagai Antitesis Pembangunan Ekstraktif di Indonesia - Muhammad Suaib Tahir; Muhammad Patri Arifin; Agam Royana; Habib Maulana Maslahul Adi; Muhsin (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
This study aims to analyze the roots of the ecological crisis in Indonesia driven by the paradigm of extractive development and to evaluate the limitations of modern regulations in providing equitable environmental protection. Although numerous studies have examined the tension between economic development and ecological sustainability, a research gap remains regarding the integration of classical Islamic legal concepts, particularly ḥimā, into a contemporary environmental law framework grounded in an ecocentric approach. Therefore, this study contributes by proposing a conceptual reconstruction of Ecocentric Fiqh through the revitalization of the ḥimā instrument as an alternative mechanism for protecting Community-Managed Areas (Wilayah Kelola Rakyat / WKR) amid the expansion of extractive development in Indonesia.This research employs a qualitative method using a juridical-normative approach and library research. Data were collected from strategic environmental reports, including Environmental Outlook 2025 published by WALHI, and were examined alongside contemporary Islamic legal literature and reputable international journal sources. The analysis was conducted to connect empirical ecological crisis data with the normative construction of Islamic law in the context of environmental protection.The findings reveal that development policies centered on economic growth have generated significant ecological debt, marked by extensive deforestation, agrarian conflicts, and investment dominance in natural resource governance. Existing positive law tends to be anthropocentric and has not yet provided substantive ecological protection. As a key finding, this study demonstrates that revitalizing the concept of ḥimā within the framework of Ecocentric Fiqh offers a more inclusive model of territorial protection by positioning nature as an entity with intrinsic value. The contribution of this study lies in developing a theoretical framework for Islamic environmental law that is not merely normative but also relevant for addressing contemporary ecological challenges in Indonesia.